Analysis of Factors Affecting the Export Potential of Indonesian Tea Plantation Products to European Countries - Darmashanty, Nathaya Andhyra; Kuncoro, Trian Gigih (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Tea is one of the commodities in the plantation sub-sector that is exported to international markets. In addition, Indonesia's land quality is suitable for tea growing conditions and has the potential to increase production and export volumes to the international market. However, in 2021, Indonesia's tea export performance declined so that productivity decreased. Limitations in technology, selection of poor quality tea seeds, and lack of government attention to the tea farming sector are the reasons for the decline in export performance in the sector. This study aims to to analyze whether the GDP of the importing country, exchange rates, inflation, and carbon dioxide (CO2) emissions affect Indonesian tea exports to importing countries. Methodology: The research method used quantitative data and was tested with multiple linear regression analysis with Ordinary Least Square (OLS) model to investigate the effect of Gross Domestic Product, inflation, exchange rate, and carbon dioxide on Indonesian tea exports from 2009-2020. Results: The results of the study showed that statistically the GDP of the UK and the Netherlands had no effect on Indonesian tea exports while the increase in GDP positively affected Indonesian tea exports to Russia. Carbon dioxide emissions have a negative effect on Indonesian tea exports to Russia, the Netherlands and the UK. Applications/Originality/Value The findings provide advice for the government to maintain tea exports as well as provide supportive agricultural media, innovations in environmentally friendly agricultural technology, and increase cooperation between tea farmers.